Instrumented cervical spinal fusions in children: Indications and outcomes. (December 2017) - Lastikka, M.; Aarnio, J.; Helenius, I.
Purpose: To report indications, outcomes and complications of instrumented cervical spinal fusion in a consecutive series of children at major university hospitals. Methods: A retrospective, single surgeon series identified 35 consecutive children with a mean follow-up (FU) of 2.5 years undergoing instrumented cervical spinal fusion between 2005 and 2015. Results: The main indications were skeletal dysplasia and trauma associated cervical instability. Surgical complications were observed in 12 (34%) patients with multiple complications in four (11%). Four (11%) children required at least one revision surgery, three for nonunion and one for graft dislodgement. All were fused at FU. Surgical complications were more common in children undergoing occipitocervical (OC) fusion than in those avoiding fusion of the OC junction (60% versus 24%) (p = 0.043). Complications were found significantly more in children operated on under the age of ten years than above (50% versus 18%) (p = 0.004). The risk of complications was not dependent on the indications for surgery (skeletal dysplasia versus trauma) (p = 0.177), Conclusion: Skeletal dysplasia associated cervical instability and cervical spine injuries represented the most common indications for instrumented cervical spinal fusion in children. Complications were observed in one-third of these children and 11% required revision surgery for complications. OC spinal fusion and spinal fusion before the age of ten years are associated with higher risk of surgical complications and increased mortality than non-OC fusions and cervical spinal fusions at an older age. We urge surgeons to employ caution to the patient, timing and procedure selection when treating paediatric cervical spine.